Is Management Science International: In Search of Universal Rules - Aharoni, Yair; Burton, Richard M. (Management Science, 1994)
In management science, as in all of science, a fundamental issue is the generalizability of what we know. It is a never-ending quest to discover and create knowledge and rules which are universal. Yet, frequently what we hold to be universal is quite specific when examined with scientific scrutiny. In this special issue of Management Science we want to develop more precisely the dimension and the extent to which what we know in management science is generalizable, e.g., is our knowledge about managing universal or specific? Is our knowledge limited to a particular firm, an industry, a given country, or a culture? The universality/specificity issue remains a dilemma. The theme of this special issue is the generalizability of management science. Management Science publishes research on theory, methodology and empirical results.